Renal Outcomes Following Fenestrated and Branched Endografting. Issue 4 (October 2015) - Martin-Gonzalez, T.; Pinçon, C.; Maurel, B.; Hertault, A.; Sobocinski, J.; Spear, R.; Le Roux, M.; Azzaoui, R.; Mastracci, T.M.; Haulon, S.
Abstract : Objective: The purpose of this study was to analyze immediate and long-term renal outcomes (renal function and renal events) after fenestrated (FEVAR) and branched endovascular aortic aneurysm repair (BEVAR). Methods: All FEVAR and BEVAR performed between October 2004 and October 2012 were included in this study. Post-operative acute renal failure (ARF) was defined according to the RIFLE criteria. Renal volume (calculated with a 3D workstation) and estimated glomerular filtration rate (GFR) (estimated with the Modification of Diet in Renal Disease [MDRD] formula) were evaluated before the procedure, before discharge, 12 months after, and yearly thereafter. Renal stent occlusion, dissection, fracture, stenosis, kink, renal stent related endoleak, and renal stent secondary intervention were all considered "renal composite events" and analyzed. A time to event analysis was performed for renal events and secondary renal interventions. Results: 225 patients were treated with FEVAR and BEVAR. Renal target vessels ( n  = 427) were perfused by fenestrations ( n  = 374), or branches ( n  = 53). Median follow up was 3.1 years (2.9–3.3 years). Technical success was achieved in 95.5% of patients. Post-operative ARF was seen in 64 patients (29%). Mean total renal volume and eGFR at 1 year, 2 year, and 3 year follow up were significantly lower when compared with pre-operative levels (after BEVAR and FEVAR); the decrease at 3 years was 14.8% (6.7%; 22.2%) ( p  = .0006) for total renal volume and 14.3% (3.1%; 24.3%) ( p  = .02) for eGFR. The 30 day and 5 year freedom from renal composite event was 98.6% (95.8–99.6%) and 84.5% (76.5–89.9%) after FEVAR and BEVAR (NS). The 30 day and 5 year freedom from renal occlusion was 99.5% (96.7–99.9%) and 94.4% (89.3–97.1%) after FEVAR and BEVAR (NS). Conclusion: FEVAR and BEVAR are durable options for the treatment of complex aortic aneurysms and are associated with low renal morbidity, without differences between devices types. The clinical impact of decreasing renal volume over time in these patients is yet to be fully understood.